Particle size distribution and settling velocity of sediments in water diverted from the Yellow River during border-strip irrigation - Li Jinshan; Fei Liangjun; Chen Zhen; Sun Xiulu (Tecnología y ciencias del agua, 2017)
Li, J., Fei, L., Chen, Z., & Sun, X. (March-April, 2017). Particle size distribution and settling velocity of sediments in water diverted from the Yellow River during border-strip irrigation. Water Technology and Sciences (in Spanish), 8(2), 31-41. Diversion of river water for irrigation is an important factor in sustainable agricultural development in the Yellow River basin. This study examines patterns in the advance of sediment in irrigation water diverted from the Yellow River during border-strip irrigation. An irrigation experiment was carried out on a 1.8 m-wide strip and a 2.7 m-wide strip of a fruit field in order to observe the advance rate of irrigation water, the distribution of settled sediment, and the concentration and particle size distribution of sediment in the water flow. The settling velocity of sediment particles was then calculated using an empirical formula. The results show that the irrigation water gradually slowed as it advanced along the strip length, and the amounts of deposited particles decreased from the top ends of the strips to their bottom ends. The decrease was especially sharp on the section of each strip between 40 and 120 m from the water pipe outlet. Overall, the size of particles carried by the irrigation water fell within the range of 0.004 to 0.016 mm, with coarse and fine particles making up small proportions of the sediment. The concentration of coarse particles was higher at the top ends than at the bottom ends, while the concentration of fine particles was higher at the bottom ends than at the top ends. Water content in the soil at several locations varied significantly before and after irrigation, and the deposition of sediment was found to exert a great influence on the infiltration of irrigation water. The particle size distribution of the sediment deposited along the strips accords with the law of sedimentation in that coarse particles accumulated primarily at the top ends of the strips as a result of high settling velocity. Moreover, the results demonstrate that it is feasible to simplify the water flow over the field to open-channel flow when calculating settling velocity. However, the formula for calculating settling velocity needs further modification to take into account the influences of flume rate and the scouring action of irrigation water on the surface sediment deposited on the strips.